ANALISIS KEJADIAN KEKURANGAN ENERGI KRONIK (KEK) PADA IBU HAMIL DI WILAYAH KERJA PUSKESMAS POASIA - Nasrawati Alwan; Wa Ode Salma; I Made Christian Binekada (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2023)
Chronic Energy Deficiency (CED) in pregnant women is a person's poor nutritional status due to an imbalance between intake and energy expenditure. The World Health Organization (WHO) reports that the global prevalence of anemia in pregnancy and CED is 35-75%, significantly increasing in the third trimester compared to the first and second trimesters of pregnancy. The purpose of this study was to determine the risk factors for KEK occurrence in pregnant women in the working area of ​​the Poasia Public Health Center, Kendari City. This type of research was observational analytic using a Case Control design involving 128 pregnant women in the working area of ​​the Poasia Health Center who were selected by purposive sampling which were divided into 2 groups namely 64 pregnant women suffering from CED and 64 normal pregnant women as the control group. The results showed that all variables were risk factors for the occurrence of CED in pregnant women with an OR > 1. The conclusion of the study was that the variables of diet, income, knowledge and culture were risk factors for the occurrence of CED in pregnant women.